Maternal infections during pregnancy and offspring midlife inflammation - Pedersen, Jolene Masters (Matern Health Neonatol Perinatol, 2019)
BACKGROUND: Microbial exposures early in life have been found to be associated with lower levels of inflammation in adulthood; however, the role of prenatal exposure to infection on offspring inflammatory profiles is unexplored. The aim was to study if maternal infections during pregnancy are associated with inflammation among offspring in later life and to determine if there are sensitive periods of exposure. METHODS: The study was comprised of 1719 participants in the Copenhagen Aging and Midlife Biobank (CAMB) who were also members of the Copenhagen Perinatal Cohort (CPC). When the CPC was established, information on maternal infections during pregnancy was prospectively collected by a trained medical doctor. The inflammatory measures collected in late midlife included, C-reactive protein (CRP), Interleukin-6 (IL-6), TNF-alpha (TNF-α) and Interleukin-10 (IL-10). Multivariable ordinary least squared regression models were implemented to explore associations between maternal infection and inflammatory measures in offspring, controlling for maternal smoking, pre-pregnancy body mass index, age, marital status and parity. RESULTS: Maternal infection was associated with a 7% lower CRP level (95% CI, − 17,5%) among offspring compared with offspring born to women without an infection and similarly an 8% lower level of IL-6 (95% CI -15,1%), and a 9% lower level of IL-10 (95% CI, − 23,20%). However, differences did not reach significance. The effects of infection during the first trimester did not differ from infections later in the pregnancy. CONCLUSIONS: Our results suggested that prenatal exposure to infection may be associated with lower levels of inflammatory markers among adult offspring. Additional prospective studies are needed to further explore this finding.